Adoption of Recommended Plant Protection Measures for the Management of Major Coconut Pests by Coconut Growers in Kurunegala District, Sri Lanka - Subhathma, W. G. Ruvani (International Coconut Community Journal, 2018)
Coconut production in Sri Lanka is threatened by pest and diseases. Therefore, different remedial measures have been introduced by Coconut Research Institute (CRI) to safeguard the plantations. This study was carried out to determine the adoption of recommended plant protection measures to manage major pests of coconut by the growers in different land categories. The growers were selected from Kurunegala district, which is the major coconut growing district in coconut triangle in Sri Lanka. Findings of the study revealed that more than 70 percent of the growers in all land categories above 2Ac had adopted technologies recommended by CRI to control black beetle. Technology adoption was around 60 percent for red weevil control, around 30 percent for coconut mite and around 65 percent for plesispa beetle. It was also noted that the decision making on the adoption of different technologies is affected by the perceptions of the growers. Growers’ perception was determined by two factors, information receiving sources and occurrence of pest attacks in their fields. Further, it was found that the growers are having limited access to latest technologies in pest control. In addition, the study revealed that unawareness of technologies and low attention for coconut farming was the two major reasons for poor adoption of the recommended technologies. It is concluded that coconut growers in Kurunegala district require more awareness regarding recommended plant protection measures to manage major coconut pests and strengthen extension programes.